The influence of ethical codes’ awareness, ethical leadership and ethical work climate on organizational commitment: The Malaysian Army’s perspective / Wan Zairibahri Wan Abdul Razak - Wan Zairibahri , Wan Abdul Razak (2021)
Organizational commitment is an attractive area of research for the business world, because it affects the employees and leadership quality. To date, only a few studies had examined the relationship of organizational commitment with ethical climate, particularly in the military context. In view of the government’s effort to improve the military organization and its structure, this study aims to investigate the relationship between the staff’s ethical aspects and their organizational commitment within the Malaysian Army. The conceptual framework was build based on the relationship that exists between staff’s ethical codes’ and ethical leadership with organizational commitment so as to investigate how the various variables influenced the dependent variable. The ethical codes’ awareness and ethical leadership served as the independent variables while organizational commitment served as the dependent variable. Ethical work climate acted as the moderating variable which would indicate its influence between the independent and the dependent variables. Five hypotheses were developed and tested based on the framework. A questionnaire that reflected the research constructs was developed for collecting primary data from 1167 Malaysian Army personnel. This quantitative study uses the Partial Least Square – Structural Equation Modelling (PLS-SEM) to validate and confirm the research model by testing the hypotheses. The findings of this study provided empirical evidence which showed the significant influence of ethical codes’ awareness, ethical leadership, and ethical work climate on organizational commitment. The PLS results further indicated that all the evaluation factors have statistical significant impact on organizational commitment. In this study, only four hypotheses were supported. The findings made a significant contribution to the organizational commitment and military ethics literature. It was thus recommended that organizations implement practices that could help to promote the awareness of ethical codes’ contents and the importance of developing ethical leadership. The outcome derived from this study endorsed the existence of ethical work climate on the relationship existing between ethical codes’ awareness and ethical leadership with organizational commitment.